在系统性硬化病中进行自身造血干细胞移植的功效和安全性:文献的系统性评述. (29th March 2018) - Eyraud, A.; Scouppe, L.; Barnetche, T.; Forcade, E.; Lazaro, E.; Duffau, P.; Richez, C.; Seneschal, J.; Truchetet, M.‐E.; ,
Abstract : Linked Article:  Eyraud et al. Br J Dermatol 2018;178 :650–658